Asian security dynamic : U.S. Japan and the rising powers - Raghavan, V. R.; Delhi Policy Group (New Delhi : Promilla & Co.Publishers in association with Bibliophile South Asia, 2008)
Contributed articles presented at an international seminar.
"Delhi Policy Group."
Includes bibliographical references and index.
Keywords: National security -- Asia